A copper(ii)-catalyzed annulative formylation of o-alkynylanilines with DMF: a single-step strategy for 3-formyl indoles. Issue 71 (7th December 2018) - Ganesan, Balaji; Senadi, Gopal Chandru; Guo, Bing-Chun; Hung, Min-Yuan; Lin, Wei-Yu
Abstract : In this paper, a copper(ii )-catalyzed reaction of o -alkynylanilines with dimethylformamide (DMF) in the presence of oxygen has been developed for synthesizing multisubstituted 3-formyl indole scaffolds. Abstract : In this paper, a copper(ii )-catalyzed reaction of o -alkynylanilines with dimethylformamide (DMF) in the presence of oxygen has been developed for synthesizing multisubstituted 3-formyl indole scaffolds. This one-pot reaction proceeds through a cascade 5- endo -dig cyclization followed by formylation to construct 1, 2-disubstituted 3-formyl indoles. The key aspects of this synthesis method are the broad substrate scope (with 38 examples), and well tolerating various functional groups. In addition, a detailed mechanism has been proposed, where DMF may serve as a carbon source for the in situ C3 formylation of the obtained indole derivatives.